Legal principles and organizational means of overcoming counteraction during the investigation of criminal offenses in the field of economic activity - Bohdaniuk, Ruslan (Archives of Criminology and Forensic Sciences, 2024)
The article emphasizes the importance of combating criminal offenses in the field of economic activity, since they cause irreparable damage to the financial and economic security of the State, business, etc. The purpose of the article is to outline the legal, organizational and tactical measures aimed at overcoming the counteraction which is committed during the investigation of criminal offenses in the field of economic activity. It is determined that the legal framework for neutralizing counteraction to an investigation is enshrined in the provisions of current legislation, which indicates that all organizational measures should comply with the provisions of law. It is found that to denote all possible forms of behavior of representatives of pre-trial investigation bodies, the concept of “means” should be used, and their traditional differentiation involves the allocation of legal (primarily criminal law and criminal procedure) and organizational means. It is determined that criminal law means provide for bringing a person to liability for committing the acts provided for in the main part of the Criminal Code of Ukraine, criminal procedural means include investigative (search) and other procedural actions, as well as measures to ensure criminal proceedings, and organizational means of neutralizing counteraction to an investigation relate to an effective combination of criminal law and criminal procedural means, comprehensive involvement of the necessary forces and means, and establishment of effective interaction, etc.